Educação científica ou educação sexual : onde encontramos a interdisciplinaridade? - Santos, Franciele Monique Scopetc dos (2012)
This research started from conflicts faced in teaching practice. With these conflicts the following problem arose: How to understand the meaning that students and high school students produce about sex education? While understanding the production of meaning is an expression of knowing what the other or others think, as soon as they use discuss about it, we question the following hypothesis: If there is a sense produced about sex education in school, then we can reflect on the same qualitatively. The objective of this analysis is to think about that quality. But to do so we will need to delimit our field theory, namely, conceptual determinations of Science Education, Sex Education, Cultural Studies, Interdisciplinarity and the Discourse Analysis. Within these five major conceptual spheres we will think the construction of our method. Our sampling method was applied in Colégio Estadual Instituto de Educação, where ten students were interviewed, we used semi-structured questionnaires, which allowed greater mobility in our sessions of investigative interviews. Analyzing the interviews we noticed a gap in the students' speech interpretation, thus we launched as methodological fundamentals of this research the need to devote the same investigative method towards teachers. We consolidated our data collection method for the analysis as follows: the interview of ten subjects from the second year of high school, between sixteen and twenty years old. We filled our Interpretative gap interviewing, Philosophy and Biology teachers. Thus, we delimited our theoretical perspective of interdisciplinarity, positioned theoretically by cultural studies. To the analysis of our interviews we base our interpretation on the concepts of discourse and meaning production of Michel Foucault. Here is the recurrence of discourse analysis in our research. Our final considerations allowed us to think of science education in the eyes of the humanities. Thus, this research ends proposing the understanding of the "matrix of meaning" and where its speakers recognize themselves, because through the interviews we realized why the meanings set out seemed obvious, "natural", so true. We conclude that our study refers to an effort to examine sex education through the language. The language allows the multiplication of relationships, and extracting from it the qualitative condition was the major effort of this analysis.